EPHA5 and SOD2 genetic variants and their link to neurofilament light chain: early detection of taxane-induced neurotoxicity in Egyptian breast cancer patients - Amira B. Kassem; Amira Abdelmonem Ahmed; Noha A. El‑Bassiouny; Gamal Omran; Mahmoud Mohamed Kamel; Ahmed El Bastawisy; Nermeen Nabeel Abuelsoud (Future Journal of Pharmaceutical Sciences)
Abstract Background Breast cancer is the leading cause of cancer-related deaths globally, with taxanes being the most commonly used chemotherapeutic agents. However, adverse effects like myelosuppression, neuropathy, and hypersensitivity reactions exist. Objective To find the association between genetic polymorphisms in SOD2 rs4880 and EPHA5 rs7349683 and taxane-induced neurotoxicity, also to prospectively evaluate the usefulness of serum neurofilament light chain (sNFL) levels as an early biomarker of development neurotoxicity in different genotypes. Methods One hundred breast cancer patients prospectively received taxane treatment. Blood samples were collected, and SOD2 and EPHA5 gene polymorphisms were detected using real-time PCR. All patients were assessed using the Common Terminology Criteria for Adverse Events v 5.0 score, and the biomarker was measured from serum using an enzyme immunosorbent assay at baseline and three months after taxanes treatment. Results The detected SOD2 (rs4880) genetic polymorphisms were AA (39%), AG (49%), GG (12%), CC (49%), TC (42%), and TT (9%) in EPHA5 (rs7349683). A statistically significant difference existed between EPHA5 C > T genotypes regarding the NFL levels and delta NFL (p value = 0.000 and 0.010, respectively). Also, there was a significant association between different EPHA5 C > T genotypes and neurotoxicity grades post-taxanes treatment (p value = 0.010). There was a statistically significant difference in fatigue associated with the EPHA5 gene (p value = 0.011). Conclusion Detecting EPHA5 genetic polymorphisms before administering taxanes is highly recommended for assessing neurotoxicity risk. NFL measurement is recommended to be used in the early identification of taxane-induced neurotoxicity.